Communication: theoretical prediction of the importance of the 3B2 state in the dynamics of sulfur dioxide - Lévêque, Camille; Taïeb, Richard; Köppel, Horst (The journal of chemical physics, 2014)
Even though the sulfur dioxide molecule has been extensively studied over the last decades, its photo-excitation dynamics is still unclear, due to its complexity, combining conical intersections, and spin-orbit coupling between a manifold of states. We present a comprehensive ab initio study of the intersystem crossing of the molecule in the low energy domain, based on a wave-packet propagation on the manifold of the lowest singlet and triplet states. Furthermore, spin-orbit couplings are evaluated on a geometry-dependent grid, and diabatized along with the different conical intersections. Our results show for the first time the primordial role of the triplet 3B2 state and furthermore predict novel interference patterns due to the different intersystem crossing channels induced by the spin-orbit couplings and the shapes of the different potential energy surfaces. These give new insight into the coupled singlet-triplet dynamics of SO2.